2006
DOI: 10.1021/es060489h
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Characterization of Adsorption and Slow Desorption of Phenanthrene Aged in Soils

Abstract: Long-term adsorption of phenanthrene to soils was characterized in a silt-loam (LHS), a sandy soil (SBS), and a podzolized soil (CNS) by use of the Polanyi−Manes model, a Langmuir-type model, and a black carbon−water distribution coefficient (K BC) at a relative aqueous concentration (C e/S w) of 0.002−0.32. Aqueous desorption kinetic tests and temperature-programmed desorption (TPD) were also used to evaluate phenanthrene diffusivities and desorption activation energies. Adsorption contribution in soils was 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…On the contrary, the fraction of PAHs adsorbed by soft OC can be relatively easy to be released by the polar extractant and thus no significant relationship was observed between the extractable PAHs and the soft OC contents. However, it is surprising that no relationship between the extractable PAHs and recalcitrant BC content was discernable although a variety of investigations have indicated that BC have a strong affinity for PAHs (Abu and Smith, 2006;Agarwal and Bucheli, 2011). This phenomenon could be ascribed to the fact that BC content accounted for only about 10% of the TOC content, much lower compared with the data reported in the previous studies (Xiao et al, 2004).…”
Section: Effects Of Soil Properties On Extractability Of Pahs In Agedmentioning
confidence: 69%
See 3 more Smart Citations
“…On the contrary, the fraction of PAHs adsorbed by soft OC can be relatively easy to be released by the polar extractant and thus no significant relationship was observed between the extractable PAHs and the soft OC contents. However, it is surprising that no relationship between the extractable PAHs and recalcitrant BC content was discernable although a variety of investigations have indicated that BC have a strong affinity for PAHs (Abu and Smith, 2006;Agarwal and Bucheli, 2011). This phenomenon could be ascribed to the fact that BC content accounted for only about 10% of the TOC content, much lower compared with the data reported in the previous studies (Xiao et al, 2004).…”
Section: Effects Of Soil Properties On Extractability Of Pahs In Agedmentioning
confidence: 69%
“…S2 in SI). Furthermore, the comparable pore diameter (about 4 times larger than the PAH molecular size) was believed to be sensitive to HOC sequestration and diffusion in geomaterials (Farrell et al, 1999;Abu and Smith, 2006). In addition, a large portion of the cumulative pore volumes (about 35e65%) in the soils came from the pores with diameters smaller than 6 nm as shown in Fig.…”
Section: Effects Of Soil Properties On Diffusion Of Pahs In Aged Soilsmentioning
confidence: 96%
See 2 more Smart Citations
“…The differences in the soil behaviours are greatest for the lower molecular weight PAHs with pyrene demonstrating the greatest discrimination in terms of its behaviour in soils A and B despite the similarities in the log K oc values for fluoranthene (4.48) and pyrene (4.23). In addition to sorption onto outer humic surfaces, it has been postulated that PAH diffusion is also controlled by the narrow meso-and micro-pores of geomaterials where these are of a comparable molecular size (Abu and Smith, 2006;Nam and Alexander, 1998). It would appear that this factor becomes important in the case of the heavier PAHs (benzo(e)pyrene and benzo(ghi)perylene) enabling them to penetrate further into soil B due to its higher coarse sand fraction (Table 1) and resulting in similar removal depths for both soils despite the higher organic content of soil B.…”
Section: Soil Depth Penetrationmentioning
confidence: 99%